Genetic diversity and population structure analysis of Indian blackberry (Syzygium cumini L.) using CAAT box‑derived polymorphism (CBDP) and start codon targeted polymorphism (SCoT) markers - Ajay Kumar; Kanhaiya Singh; Amit Kumar Singh; Jai Prakash; Amit Kumar Goswami; Gyan Prakash Mishra; Vishaw Bandhu Patel; Suman Lata; Anshuman Singh (Journal of Genetic Engineering and Biotechnology)
Indian blackberry (Syzygium cumini L.) also known as jamun is a very important underutilized fruit crop with notable medicinal and economic value. However, its genetic improvement has been constrained by limited knowledge of the genetic diversity within existing collections. Therefore, a comprehensive characterization of genetic diversity in this species, using molecular tools, is essential to support effective germplasm management and application in breeding programs. In this investigation, a total of 32 jamun genotypes consisting of 30 seedling-origin genotypes, one improved cultivar CISH J-37 and one wild genotype (Syzygium fruitecosum) were analysed using the two gene-targeted markers, CBDP and SCoT. In total, 29 primers (22 CBDP and 7 SCoT primers) detected genetic polymorphism across the genotypes. The CBDP markers amplified a higher polymorphism percentage, 94.85% across 291 bands, than the SCoT markers, 92.75% across 69 bands. The mean PIC values for CBDP and SCoT were 0.28 and 0.31, respectively. MI values were higher for CBDP (3.21) than for SCoT (2.88). Cluster analysis using UPGMA identified six clades, which grouped genotypes into seedling-origin, improved and wild categories. The PCoA based on molecular profiling data of CBDP, SCoT and both together explained 26.65%, 38.39% and 23.22% of the variation respectively. AMOVA results revealed that 85–90% of genetic variation existed within populations. Bayesian STRUCTURE analysis grouped genotypes into two major populations confirming genetic divergence between seedling-origin, improved and wild genotypes. This study is the first to integrate CBDP and SCoT markers for genetic diversity analysis of the Indian blackberry. The results highlight the utility of these markers in genetic variation assessment and would help design germplasm conservation and breeding strategies in this crop.